The friars in the Philippines - Coleman, Ambrose; iGLibrary (online resource). (Boston Marlier, Callanan, 1899)
"The following pages originally appeared as magazine articles. In both England and America the papers were favorably received; and as the public has not heard the last of the Friars in the Philippines, it seemed worth while to reproduce them in the more permanent form of a small volume, making such corrections and additions as might be deemed advisable. Whatever may be the shortcomings of the book, there is a real and pressing need for the information it contains, and this need must remain the excuse for its imperfections."
The friars in the Philippines -- PREFACE -- CONTENTS -- CHAPTER I. THE WORK OF THE RELIGIOUS ORDERS IN THE PHILIPPINES -- CHAPTER II. THE CHARGES MADE AGAINST THEM CONSIDERED -- CHAPTER III. THE REBELLION LARGELY THE WORK OF A SECRET ORGANIZATION -- CHAPTER IV. THE REBELS AND THEIR GRIEVANCES -- CHAPTER V. THE SECTARIAN MISSIONARY MOVEMENT -- POSTSCRIPT -- APPENDIX.
"Originally appeared as magazine articles"--p. 3.
Includes bibliographical references and index.
Electronic Reproduction.
Keywords: Monasticism and religious orders -- Philippines; Electronic books